Implementation of Civil Sanctions against Defaulting Customers at the Tirta Daroy Regional Drinking Water Public Company Banda Aceh City - Muhammad Ilham Fauzi; Teuku Ahmad Yani; Muhammad Jafar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Qanun of Banda Aceh City Number 4 of 2022 emphasizes that the Tirta Daroy Regional Public Company of Drinking Water aims to provide fair and sustainable drinking water services. The legal relationship between the customer and the company is regulated through the Decree of the Board of Directors PEG Number. III/10/PDAM/2020. However, there are still many customers who are in default in the form of late payments that cause losses to the company and are contrary to Article 1243 of the Civil Code regarding the obligation of debtors to compensate for losses due to negligence. This study aims to analyze the default settings in the customer connection agreement at the Tirta Taroy Regional Public Drinking Water Company , identify the factors causing defaults, and explain the form of applying civil sanctions to customers who commit defaults. This study uses an empirical juridical method with qualitative descriptive analysis based on legal and field data. The results of the study show that the most dominant forms of default in customers of the Tirta Daroy Regional Drinking Water Public Company are late and arrears of payments, not paying at all and misuse of water connections. The main causative factors include economic conditions, administrative negligence, and intentional elements. Legally, this default causes financial losses and disrupts the sustainability of public services. Sanctions are applied in stages through notices, warnings, summonses, to fines, compensation, or disconnection. The Tirta Daroy Regional Public Company is advised to follow up on customer complaints, improve the billing system, adjust the sanction clause proportionately, and increase legal awareness through socialization.